Evaluation of knowledge, attitude and practice of students' parents about fissure sealant therapy - Golestan B; Amir Soltani M; Jafari A; Bahrami N (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Fissure sealant therapy is a national program in elementary schools in Iran. Therefore, evaluation of the parents' knowledge and attitude is necessary to improve the program."nMaterials and Methods: In this cross-sectional and descriptive-analytic study, Iranian students were chosen in a randomized cluster manner. The questionnaires were filled-out by students' parents to evaluate their general information, knowledge, and attitude. Moreover, students were examined for having any fissure-sealed teeth. Data were collected and analyzed by multiple logistic regression tests."nResults: 414 boy students and their parents were participated in this study. 57.6% of parents knew that fissure sealant prevents the caries and 44.5% believed that fissure sealant is important to prevent caries. However, only 8.9% of children had fissure sealant. Parents' knowledge was significantly related to the source of oral health information and oral health education. Regular dental visits and high level education was effective in increasing the knowledge about sealant therapy. There was a significant relation between parents' attitude toward fissure sealant and level of education, oral health education and numbers and times of dental visit (P<0.001). There were a significant relation between tooth sealing and parents' oral health information."nConclusion: Regular dental visits and oral health education have positive role in parent's knowledge and attitude and practice. So parents must be encouraged to have regular dental visit and dentists must be emphasized to give them necessary education. School is the best place for giving proper information to parents.